Ambivalence of Identity and Dislocation Seen in Lotus Eater by W. Somerset Maugham and The Prisoner Who Wore Glasses by Bessie Head - Christoforus Sigi Bramaditya (Indonesian Journal of English Language Studies (IJELS), 2019)
This paper focuses on identifying the ambivalence and displacement seen in two short stories. The first is Lotus Eater by W. Somerset Maugham and the second is The Prisoner Who Wore Glasses by Bessie Head. Both of the stories tells us about the cultural contact which occur in the colonial era where there are differences of culture and power operate. This paper uses Bhabhas theory of ambivalence and dislocation in order to scrutinize the ambivalence and dislocation in the two short stories. This research paper finds out that in those stories, the ambivalent identity and sense of dislocation emerge and affect to both sides interacting in the cultural contact. Both the ambivalent identity and the sense of dislocation operate together to tell the complex relation of the entities inside the stories.Keywords: cultural contact, ambivalent identity, displacement